Sintomas vocais e a qualidade vocal de professores após exposição vocal em sala de aula - Santos, Jennifer Paola Alves dos (2023)
Introduction: Vocal fatigue (VF) can be identified through auditory and tactile signs and symptoms such as: hoarseness, breathiness, loss of vocal power and dryness in the larynx and pharynx. Objective: To analyze the vocal symptoms and vocal quality of male teachers after vocal exposure in the classroom. Methodology: This is a study with a comparative and descriptive approach, in which the vocal symptoms and vocal quality of teachers were compared before and after vocal exposure in the classroom. Vocal samples and self-assessment protocols were recorded before and after vocal exposure. The ITDV (Voice Disorder Screening Index and QVV (Voice Quality of Life)) protocols were applied only before vocal use. Statistical analysis was performed using the jamovi software and the significance level for comparative analyzes was p<0 ,05 Results: There was a slight increase in the mean fundamental frequency, jitter and shimmer after vocal exposure and only hoarseness was the variable with slight alteration after vocal exposure. if evidenced before and after vocal use. In the auditory-perceptual judgment of the voices, there was alteration in the variable breathiness after prolonged exposure of the voice. The presence of hoarseness symptoms, voice failure and dry throat was observed with a score rarely in the ITDV and of no there was an impact on the vocal quality of life.Conclusion: Succinct vocal alterations were evidenced after vocal exposure in these studied teachers.